2009
DOI: 10.1007/s00432-009-0665-6
|View full text |Cite
|
Sign up to set email alerts
|

Quality of life among elderly men treated for prostate cancer with either radical prostatectomy or external beam radiation therapy

Abstract: Both aggressive treatments can offer satisfactory functional outcomes from the perspective of HRQOL for selected elderly subjects with localized prostate cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
12
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 28 publications
5
12
0
Order By: Relevance
“…The results of the present study were similar to those of previous studies, in which patients treated by brachytherapy or SRT were prospectively assessed using the SF-36 HRQOL questionnaire [11,15]. Specifically, those who underwent external beam radiotherapy reported no significant changes with regard to general HRQOL between pre-and post-treatment [12,14]. In our study, there was a significant decline in the PCS score at I-SRT compared to that at the baseline (45.2 ± 11.9 vs. 47.9 ± 12.3, P = 0.04, Table 3), which was restored by F-SRT-1.…”
Section: Domainssupporting
confidence: 78%
See 1 more Smart Citation
“…The results of the present study were similar to those of previous studies, in which patients treated by brachytherapy or SRT were prospectively assessed using the SF-36 HRQOL questionnaire [11,15]. Specifically, those who underwent external beam radiotherapy reported no significant changes with regard to general HRQOL between pre-and post-treatment [12,14]. In our study, there was a significant decline in the PCS score at I-SRT compared to that at the baseline (45.2 ± 11.9 vs. 47.9 ± 12.3, P = 0.04, Table 3), which was restored by F-SRT-1.…”
Section: Domainssupporting
confidence: 78%
“…Moreover, many longitudinal studies have demonstrated the impact of primary radiotherapy to the prostate on health-related quality of life (HRQOL) using several measurement tools such as the Medical Outcomes Study 36-Item Short Form health survey (SF-36) and the University of California, Los Angeles-Prostate Cancer Index (UCLA-PCI) [11][12][13][14]. Several domains such as the urinary and bowel function domains, showed transient deterioration in the first years following brachytherapy [11,12].…”
mentioning
confidence: 99%
“…A number of important outcomes of surgical treatment and radiation therapy could not be evaluated due to the retrospective nature of our study, including quality of life (which has been investigated in previous research) [21, 22]. In these studies, quality of life was found to be comparable for both RP and EBRT treatment, with all aspects of quality of life being well-maintained with the exception of sexual function.…”
Section: Discussionmentioning
confidence: 96%
“…For patients with early-stage cancer and low-risk disease, excellent long-term survival has been reported after treatment with both radical prostatectomy (RP) and radiotherapy [2]. Because more favorable survival outcomes have become the norm, the basis on which patients select primary therapy has shifted towards considering health-related quality of life (HRQoL) [3][4][5][6].…”
Section: Introductionmentioning
confidence: 99%